Genetic etiology of autism spectrum disorder in the African population: a scoping review - Hakizimana, Olivier; Hitayezu, Janvier; Uyisenga, Jeanne P.; Onohuean, Hope; Palmeira, Leonor; Bours, Vincent; Alagbonsi, Abdullateef Isiaka; Uwineza, Annette (Frontiers in Genetics, 2024)
Background: Autism spectrum disorder (ASD) is a neurodevelopmental disorder (NDD) characterized by significant impairments in social, communicative, and behavioral abilities. However, there are limited studies addressing the genetic basis of ASD in the African population. This study aims to document the genes associated with ASD in the African population and the techniques used to identify them. Additionally, genes identified elsewhere but not yet in Africa are also enumerated. Methods: Online databases, such as Wiley Online Library, PubMed, and Africa Journal Online (AJOL) were used. The review was conducted using the keyword related to genetic and genomic ASD study in the African population. Result: In this scoping review, 40 genetic studies on ASD in Africa were reviewed. The Egyptian and South African populations were the most studied, with 25 and 5 studies, respectively. Other countries with fewer studies included Tunisia (4), East African countries (3), Libya (1), Nigeria (1) and Morocco (1). Sixty-one genes responsible for ASD were identified in the African population: 26 were identified using a polymerase chain reaction (PCR)-based method, 22 were identified using sequencing technologies, and 12 genes and one de novo chromosomal aberration were identified through other techniques. No African study identified any ASD gene with genome-wide association studies (GWAS). Notably, at least twenty ASD risk genes reported in non-African countries were yet to be confirmed in African population. Conclusion: There are insufficient genetic studies on ASD in African population, with sample size being a major limitation in most genetic association studies conducted, leading to inconclusive results. Thus, there is a need to conduct more studies with large sample size to identify other genes associated with ASD in African population using high-throughput sequencing technology.